State Laws on Substance Use Treatment for Incarcerated Pregnant and Postpartum People - Mollee K Steely Smith; Melissa J Zielinski; Carolyn Sufrin; Camille T Kramer; Sara J Benning; Rosemary Laine; Rebecca J Shlafer (SAGE Publishing, 2023)
Background: Incarcerated perinatal populations report high rates of substance use in the United States (US). Despite this, substance use disorder (SUD) treatment is not routinely available in carceral settings and state policies related to the provision of substance use screening and treatment are unknown. Methods: We conducted a systematic search in WestLaw through the end of the 2020 legislative session combining the terms "pregnant" and "postpartum" with terms for incarceration and related terms. The search returned 453 statutes from 43 states. A deductive codebook of various maternal health topics was developed. Legislative texts related to SUD screening and treatment were extracted for textual analysis. Results: Of the 43 states identified as having at least 1 state statute pertaining to pregnant or postpartum incarcerated people, 7 states had statutes relevant to SUD screening and treatment. Statutes related to substance use screening, education, treatment and diversion programs, program eligibility, aftercare and release planning, and funding appropriations. Conclusions: The majority of states across the U.S. lack legislation that address SUD screening and treatment among incarcerated perinatal populations. Given the known limited access to SUD treatment for perinatal populations in custody, increasing legislative statutes could increase access to essential care.